2009
DOI: 10.1002/cbf.1627
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of adenosine deaminase activity and increase of the lipid peroxidation after acute methotrexate treatment in young rats: protective effects of grape seed extract

Abstract: The methotrexate (MTX) is an anti-folate used to treat cancer and some inflammatory diseases. The efficacy of MTX is often limited by its severe toxicity. The present study was undertaken to determine whether Grape seed (Cabernet Sauvignon) extract (GSE) could ameliorate the MTX-induced oxidative injury and the effect on adenosine deaminase activity (ADA) in rats. The rats were pretreated with 50 mg/kg of GSE, i.p., prior to MTX administration (10 mg/kg, i.p.) with a second dose given 4 h and a third dose 16 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…As may be observed in this study, MTX caused liver and kidney injuries by oxidative damage. Although the mechanism of MTX-induced hepatorenal toxicity is not well understood, recent studies indicated the oxidative damage to be the causative factor (19). It had been shown that the cytosolic NADP-dependent dehydrogenases and NADPmalic enzymes were inhibited by MTX, suggesting that the drug could either decrease the availability of reduced NADPH in cells (12) or NADPH was used by GSH reductase to reduce an important cytosolic antioxidant, GSH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As may be observed in this study, MTX caused liver and kidney injuries by oxidative damage. Although the mechanism of MTX-induced hepatorenal toxicity is not well understood, recent studies indicated the oxidative damage to be the causative factor (19). It had been shown that the cytosolic NADP-dependent dehydrogenases and NADPmalic enzymes were inhibited by MTX, suggesting that the drug could either decrease the availability of reduced NADPH in cells (12) or NADPH was used by GSH reductase to reduce an important cytosolic antioxidant, GSH.…”
Section: Discussionmentioning
confidence: 99%
“…The significant reduction in GSH levels promoted by MTX could cause two results: first, in conjunction with reduced GSH levels, inactivation of reactive molecules; second, the tendency of covalent bonding with other macromolecules increases. This could lead to a reduction in effectiveness of the antioxidant enzyme defense system, sensitizing the cells to ROS (19). Tissue CAT is an important oxidant detoxifier, playing a key role in the elimination of lipid peroxides and H 2 O 2.…”
Section: Discussionmentioning
confidence: 99%
“…These molecules possess a structure that confers on them an antioxidant property, which has been demonstrated to exert a novel spectrum of biological, pharmacological, therapeutic, and chemoprotective effects against oxygen free radicals and oxidative stress, which can be used as herbal remedies especially for controlling oxidative damages (El-Ashmawy et al, 2007and Dulundu et al, 2007. Several studies have indicated that extracts obtained from grape seed inhibit enzyme systems that are responsible for the production of free radicals, and that they are antimutagenic and anticarcinogenic (Pinheiro et al, 2010). For this reason, grape seed extract is widely consumed as a dietary supplement in addition to the chemotherapeutic agents in cancer treatment (cetin et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…[28][29][30][31] One of them, GE, was mostly emphasized on its antioxidant properties in a number of in vitro and in vivo studies. 17,32,33 Various studies also presented that GE has been tried in the repair of MTX-induced intestinal injury. In the present study, the dilution of the concentrated GE which included skin, seed and juice was tried after inducing intestinal damage with MTX.…”
Section: Discussionmentioning
confidence: 99%